\[\boxed{\text{412\ (412).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ x^{2} - 8x + 7 =\]
\[= (x - 1) \cdot (x - 7)\]
\[Получим\ из\ правой\ части\ \]
\[левую:\]
\[x^{2} - 8x + 7 =\]
\[= x^{2} - 7x - 1x + 7\]
\[x^{2} - 8x + 7 = x^{2} - 8x + 7.\]
\[Тождество\ доказано.\]
\[2)\ y^{2} \cdot (y - 7) \cdot (y + 2) =\]
\[= y^{4} - 5y^{3} - 14y^{2}\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[\left( y^{3} - 7y^{2} \right) \cdot (y + 2) =\]
\[= y^{4} - 5y^{3} - 14y^{2}\]
\[y^{4} + 2y^{3} - 7y^{3} - 14y^{2} =\]
\[= y^{4\ } - 5y^{3} - 14y^{2}\]
\[y^{4} - 5y^{3} - 14y^{2} =\]
\[= y^{4} - 5y^{3} - 14y^{2}.\]
\[Тождество\ доказано.\]
\[3)\ a^{3} - 8 =\]
\[= (a - 2) \cdot (a^{2} + 2a + 4)\]
\[Получим\ из\ правой\ части\ \]
\[левую:\]
\[a^{3} - 8 = a^{3} - 8.\]
\[Тождество\ доказано.\]
\[4)\ (a - 1) \cdot (a + 1) \cdot \left( a^{2} + 1 \right) =\]
\[= a^{4} - 1\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[(a - 1)\left( a^{3} + a^{2} + a + 1 \right) =\]
\[= a^{4} - 1\]
\[a^{4} - 1 = a^{4} - 1.\]
\[Тождество\ доказано.\]
\[Получим\ из\ левой\ части\ \]
\[правую:\]
\[a^{8} + a^{4} + 1 = a^{8} + a^{4} + 1.\]
\[Тождество\ доказано.\]
\[\boxed{\text{412.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 5y^{3} - (6y + 1) = 19 - 2y + 5y^{3}\]
\[5y^{3} - 6y + 1 + 2y - 5y^{3} = 19\]
\[- 4y = 19 - 1\]
\[- 4y = 18\]
\[y = - \frac{18}{4} = - \frac{9}{2}\]
\[y = - 4,5.\]
\[2)\ 7x - 2x^{2} - \left( 10 - 2x^{2} \right) = 11\]
\[7x - 2x^{2} - 10 + 2x^{2} = 11\]
\[7x = 21\]
\[x = 3.\]
\[3)\ 8x^{2} + 6x - \left( 2x + 8x^{2} - 12 \right) = 4\]
\[8x^{2} + 6x - 2x - 8x^{2} + 12 = 4\]
\[4x = - 8\]
\[x = - 2.\]